Learning English in unprivileged Ecuadorian contexts: Parents’ perceptions and attitudes in early education - Gabriela Galeas; Sandy Cedeño; Keren Mendoza; Gabriela Paredes; Johnny Briones (Studies in English Language and Education, 2026)
Teaching English at pre-primary levels is widely observed in more privileged educational contexts, where stakeholders view it positively. The purpose of this study is to examine the perceptions and attitudes of a group of parents (or guardians) regarding the introduction of English into public preschool education. This mixed-methods research study examined the perceptions and attitudes of 263 parents from three public kindergartens in Ecuador, whose children were learning English as part of an English program implemented by a public university for approximately four months. A 10-item Likert scale questionnaire (Cronbach’s alpha = 0.98) and an open-ended question questionnaire were employed at the end of the English program. Quantitative data were analyzed descriptively, and qualitative data were treated thematically. Research data showed that parents appear to be positive about the benefits of learning English and its integration at an early age. The findings also revealed that guardians witnessed and perceived cognitive and social benefits of learning English in preschool. Additionally, parents provide information on ways to support English learning at home, regardless of their socioeconomic status. This paper concludes by discussing the implications of parents as key stakeholders in supporting English in early education in the Ecuadorian context, as well as their role in bridging gaps in learning opportunities, and the introduction of English in strategic and vulnerable contexts. Therefore, understanding parents’ perceptions of early English instruction empowers policymakers to design preschool curricula that are culturally responsive, widely accepted, and grounded in the real needs and expectations of the community.